ARMENIAN MUSIC IN TRANSYLVANIA – THE MUSICAL HERITAGE OF THE CANTOR BÁLINT ÁKOS - Ágota BODURIAN (Studia Universitatis Babeş-Bolyai. Musica, 2020)
The author of this study is deeply preoccupied with the culture and music of an ethnic group in Transylvania that us on its way to extinction: Armenians. During our research in documenting the archives and libraries of the Armenian-Catholic parishes in the area, some materials of special value were discovered that had not yet been catalogued, representing proof of an effervescent musical life, demonstrating a rich liturgical activity, a religious life experienced deeply, in which music constituted an indispensable part of the life of the Armenian community in Gheorgheni. At the same time, these musical materials remind us about the close-knit relationships among various Armenian communities in Transylvania (Gherla, Gheorgheni, Frumoasa, and Dumbrăveni), and about the mutual influences between the ethnic cultures that coexist within the Transylvanian communities: Romanian, Hungarians, and Armenians.